Primary Neonatal Diaphragmatic Abscess - Zouari, Mohamed; Jallouli, Mohamed; Ben Thabet, Afef; Ben Dhaou, Mahdi; Gargouri, Abdellatif; Mhiri, Riadh (Journal of Neonatal Surgery, 2015)
Neonatal diaphragmatic abscesses are extremely rare and they usually develop by direct extension from a liver abscess. The first case of primary diaphragmatic abscess in a neonate is reported and the difficulties of diagnosing this rare entity are discussed.